Volumetric changes of the upper airway following maxillary and mandibular advancement using cone beam computed tomography. Issue 2 (February 2019) - Parsi, G.K.; Alsulaiman, A.A.; Kotak, B.; Mehra, P.; Will, L.A.; Motro, M.
Abstract: The objective of this project was to retrospectively evaluate changes in volume of different compartments of the upper airway in response to maxillary, mandibular, and bimaxillary advancement surgeries and to predict the extent of volumetric changes associated with these surgical movements. Pre- and post-surgical cone beam computed tomography scans of 36 patients were evaluated for changes in nasal cavity, nasopharyngeal, oropharyngeal, and hypopharyngeal compartments. The amount of movement for each surgery was measured from skeletal landmarks to reference planes and was correlated with volumetric changes. Maxillary advancement of 4.0 ± 2.2 mm increased the oropharyngeal volume significantly (41.40%), and mandibular advancement of 3.8 ± 1.6 mm also significantly increased the oropharyngeal volume (21.17%). Bimaxillary advancement of 5.1 ± 1.3 mm for the maxilla and 6.4 ± 3.1 mm for the mandible significantly increased nasopharyngeal (27.45%), oropharyngeal (66.39%), and hypopharyngeal (52.48%) volumes. Furthermore, for every millimeter anterior movement, oropharyngeal volume increased by 2319.2 ± 771.8 mm 3 . Bimaxillary advancement showed a greater increase than isolated maxillary and mandibular advancement in all pharyngeal compartments. Every millimeter of advancement in the bimaxillary group led to a significant increase in oropharyngeal volume, while every millimeter downward movement showed a significant increase in nasopharyngeal volume.